Nearly Zero Energy Building (NZEB) Materials, Design and New Approaches - Bienvenido-Huertas, David (IntechOpen, 2022)
Reducing the impact of climate change is one of the main challenges of today's society. As such, it is necessary to reduce the high energy consumption that comes with constructing and using buildings. Current energy policies are promoting decarbonization of the built environment using the nearly zero-energy building's concept. This book presents information on nearly zero-energy buildings, including materials, design, and new approaches.